2018
DOI: 10.1371/journal.ppat.1006928
|View full text |Cite
|
Sign up to set email alerts
|

ROS and Trypanosoma cruzi: Fuel to infection, poison to the heart

Abstract: The activation of macrophage respiratory burst in response to infection with Trypanosoma cruzi inflicts oxidative damage to the host’s tissues. For decades, the role of reactive oxygen species (ROS) in the elimination of T. cruzi was taken for granted, but recent evidence suggests parasite growth is stimulated in oxidative environments. It is still a matter of debate whether indeed oxidative environments provide ideal conditions (e.g., iron availability in macrophages) for T. cruzi growth and whether indeed RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 90 publications
(162 reference statements)
2
66
0
2
Order By: Relevance
“…Thus, in contrast to the msh2 mutants, the rapid generation of msh6-/-may not have allowed the mutated parasites to adapt their metabolism to cope with the oxidative stress response in the absence of a MMR protein (Grazielle-Silva et al, 2015). Recent evidence suggests that an oxidative environment is favorable for intracellular parasite survival and infection (Paiva et al, 2018). The parasite has an arsenal of enzymes to assure infection and keeps homeostasis while going into different redox environments inside the hosts (Mesías et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in contrast to the msh2 mutants, the rapid generation of msh6-/-may not have allowed the mutated parasites to adapt their metabolism to cope with the oxidative stress response in the absence of a MMR protein (Grazielle-Silva et al, 2015). Recent evidence suggests that an oxidative environment is favorable for intracellular parasite survival and infection (Paiva et al, 2018). The parasite has an arsenal of enzymes to assure infection and keeps homeostasis while going into different redox environments inside the hosts (Mesías et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Because we observed that msh6 mutants are more sensitive to H 2 O 2 treatment, we investigated whether deletion of msh6 gene affects parasite intracellular survival and amastigote multiplication. Different from T. brucei, T. cruzi has a part of its life cycle as an intracellular amastigote stage, which must cope with the generation of ROS by infected cells (Paiva et al, 2018). We investigated the role of MSH6 in response to the oxidative stress generated by two different cell types: epithelial cells and intraperitoneal macrophages extracted from BALB/c mice.…”
Section: T Cruzi Msh6 Null Mutants Display Impaired Mmr and Increasementioning
confidence: 99%
“…Another toxin, H 2 O 2 , used as the positive control, also failed to increase the level of ROS production but instead produced a slight decrease. Although the harm of superabundant ROS production to the parasites has largely been documented, it was nonnegligible that a moderate ROS level was also a promoter of their propagation, as argued by some researchers in reports of studies of Trypanosoma cruzi (38,39). Therefore, we conceived of the idea that the extremely low level of ROS production might be a result of the significantly elevated SOD activity induced by resveratrol in 12 h, and it undermined the physiological redox biological signaling, thereby interfering with the metabolism or proliferation ability of the parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ROS mobilizes intracellular iron which is essential as a cellular factor for amastigote division [30,36]. ROS, including mitochondrial ROS, contribute to oxidative damage that persists during the chronic stage of infection and is involved in the functional impairment of the heart [40][41][42]. Some studies show that cardiac parasite load may vary after treatment with antioxidants but depend on the animal model and the strain used [42][43][44].…”
Section: Murine Models Of Chagas Disease and Rosmentioning
confidence: 99%
“…ROS, including mitochondrial ROS, contribute to oxidative damage that persists during the chronic stage of infection and is involved in the functional impairment of the heart [40][41][42]. Some studies show that cardiac parasite load may vary after treatment with antioxidants but depend on the animal model and the strain used [42][43][44]. In fact, Gupta and collaborators [45] demonstrated that T. cruzi infection increases ROS production in cardiomyocytes and this effect is augmented by the pro-inflammatory cytokines.…”
Section: Murine Models Of Chagas Disease and Rosmentioning
confidence: 99%